SISTEM INFORMASI GEOGRAFIS PERSEBARAN SEKOLAH DI KOTA TASIKMALAYA BERBASIS WEB - Adiwisastra, Miftah Farid; Rahmani, Alfia; Purnia, Dini Silvi; Mulyani, Yani Sri (Universitas Nusa Cendana, 2023)
Tasikmalaya City is one of the cities in the West Java which has an area of around 184.2 km². According to data from the Ministry of Education and Culture, in Tasikmalaya City there are at least 543 schools consisting of 284 Elementary School, 142 Junior High School, 66 Senior High School and 51 Vocational High School. The purpose of this research was to create a web-based system or application that made it easier for visitors to find the distribution and location of schools in Tasikmalaya City more accurately. The method in this research used the Waterfall in software development because it was very suitable for building web-based geographic information system software. Geographic Information System is a computer system that has the abilities to write, record, store, analyse, and display geographic data. This ability can provide benefits in presenting very accurate location information with the help of the Google Map API owned by Google Map, making it easier for programmers to develop a Map on the Website. Web-based Geographic Information System for the distribution of schools in Tasikmalaya City can give information the location of school accurately and make easier to find it.